1990
DOI: 10.1021/bi00491a007
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of metarhodopsin formation by cholesterol-induced ordering of bilayer lipids

Abstract: The effect of lipid ordering on the kinetics and extent of metarhodopsin II (meta II) formation was evaluated in bovine rhodopsin which had been reconstituted into phosphatidylcholine vesicles containing 0, 15, and 30 mol% cholesterol. The rate of establishment of the dynamic equilibrium between metarhodopsin I (meta I) and the two kinetically distinguished forms of meta II in the branched meta II model [meta IIfast and meta IIslow; Straume, M., Mitchell, D. C., Miller, J. L., & Litman, B. J. (1990) Biochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
129
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(147 citation statements)
references
References 20 publications
18
129
0
Order By: Relevance
“…The equilibrium orientational distribution properties of DPH are summarized by the derived parameter f v . We have shown previously that K eq increases with increasing f v (16,18,30). In disk membranes, ethanol, butanol, and hexanol caused a concentration dependent increase in f v , while decanol induced a decrease in f v , Fig.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The equilibrium orientational distribution properties of DPH are summarized by the derived parameter f v . We have shown previously that K eq increases with increasing f v (16,18,30). In disk membranes, ethanol, butanol, and hexanol caused a concentration dependent increase in f v , while decanol induced a decrease in f v , Fig.…”
Section: Resultsmentioning
confidence: 66%
“…MII binds and activates the visual G protein, transducin (12, 13). MII formation increases with higher levels of phospholipid acyl chain unsaturation (14 -17) and decreasing levels of cholesterol (16,18).Differentiating between the two proposed mechanisms of action of alcohols and general anesthetics is difficult. However, studying the lipid dependence of the dose-response behavior of receptors in reconstituted systems is an explicit way of determining the lipid involvement in the action of these molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their studies demonstrated that systematic changes in the cholesterol composition of reconstituted phosphatidylcholinerhodopsin vesicles has profound changes on the formation of R*. These changes correspond to changes in the dynamics of the bilayer hydrocarbon region [67][68][69][70][71]. These studies indicate that cholesterol can exert an effect on rhodopsin function by reducing the partial free volume in the hydrocarbon core of the bilayer.…”
Section: Cholesterol and Rhodopsin Function In Reconstituted Rhodopsimentioning
confidence: 97%
“…It was frequently reported to regulate GPCR signaling (Oates and Watts, 2011). The effect of cholesterol on the order and fluidity of the membrane may be an important parameter for receptor function (Mitchell et al, 1990), but direct cholesterol-receptor interactions have also been described (Albert et al, 1996). Remarkably, the effect of cholesterol on GPCR function is receptor dependent.…”
Section: Rm and Hmnsmentioning
confidence: 99%